Incentives for Italian exporters : an opportunity for close cooperation between banks in Italy and abroad (Rome: Banco Di Roma, 1986)
The book presents an outline of the Italian system of assistance to exporters. A comparison with the situation before the enactment of Law 227 shows many improvements both in terms of range of application and in efficiency. Focus is being made on one major aspect, the opening up of the system to bring in foreign banks and credit institutions. Bringing in Italian "ordinary" banks which usually operate only in the short term market and by granting special ceiling to these banks which are now empowered to do medium term business in the export credit sector.
osc 28/07/16
Loans
Keywords: Export trade promotion; Italian exporters; Italy